The Lateralization of Resting Motor Threshold to Predict Medication-Mediated Improvement in Parkinson’s Disease - Tomoo Mano; Kaoru Kinugawa; Shigekazu Fujimura; Kazuma Sugie (Brain Sciences, 2022)
Cortical stimulation patterns in patients with Parkinson’s disease (PD) are asymmetric and get altered over time. This study examined cortical neurophysiological markers for PD and identified neurophysiological markers for lateralization in PD. We used transcranial magnetic stimulation (TMS) to study corticospinal and intracortical excitability in 21 patients with idiopathic PD. We used the Movement Disorder Society Unified Parkinson’s Disease Rating Scale for examination during on and off periods and evaluated inhibitory and facilitatory process markers using TMS, including resting motor thresholds (RMT), active motor thresholds, and motor evoked potential amplitude. The RMT in the more affected cortex was significantly shorter than in the less affected cortex, and was strongly correlated with improved motor function following medication. Patients in the tremor group exhibited significantly lower RMT compared to those in the akinetic-rigid group. Cortical electrophysiological laterality observed in patients with PD may be a useful marker for guiding treatment and identifying underlying compensatory mechanisms.